Ambient air pollution exposure and effects on neutralizing antibody titers following SARS-CoV-2 vaccination in adults. - Daniel P Croft; Carl J Johnston; Angela R Branche; David Q Rich; Philip K Hopke; Kelly Thevenet-Morrison; Sally W Thurston; Todd A Jusko; Md Rayhanul Islam; Catherine Bunce; Michael C Keefer; Edward E Walsh; et al. (PLOS Global Public Health)
We examined the association between air pollution and neutralizing antibody responses to COVID-19 vaccination in participants enrolled in a phase 3 clinical trial. Seventy-four adults were vaccinated with two doses of the AstraZeneca ChAdOx1 vectored vaccine (AZD1222) (5 x 1010 viral particles) at baseline and day 29, between Aug 28, 2020, to Jan 15, 2021, in Monroe County, NY. SARS-CoV-2 pseudovirus neutralizing ID50 titers (NAb) and total spike protein IgG were assessed at baseline and 15, 29, 43, 57 and 90 days after vaccination. In this pilot study, each participant's dates of neutralization titers were matched to Monroe County ambient concentrations of fine particles (PM2.5; ≤ 2.5 µm), black carbon (BC; marker of traffic), among other particulate and gaseous pollutants. Using linear mixed models, we estimated the association between each interquartile range (IQR) difference in air pollutant concentrations in the 14 days prior to blood collection and antibody responses at each post vaccination timepoint. Though not statistically significant, we observed a 23% reduction in NAb titer (95% CI: -67%, 79%) measured on day 43 (i.e., 14 days after second vaccination) associated with each 0.32 µg/m3 increase in BC concentrations in the prior 14 days. We also observed a 42% increase in spike protein IgG (95% CI: -16%, 141%) measured on day 15 (i.e., 14 days after primary vaccination) associated with each 0.26 µg/m3 increase in BC concentrations in the 14 days prior. A similar pattern for total spike protein IgG was observed at day 29 (42%; 95% CI: -22%, 157%) and 90 (43%; 95% CI: -11%, 127%). Future research will need to explore the possible association between air pollution exposure and antibody response to SARS-CoV-2 vaccination given the potential for compromised vaccine efficacy.